Gambaran Kepesertaan JKN Tahun 2019 - Silvia Nurvita (Magister Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Diponegoro, 2019)
National Health Insurance (JKN) is a program of the National Social Security System with the principle of social health insurance that is mandatory for the Indonesian population under Law No. 40 of 2004. The National Health Insurance has been implemented by the BPJS since January 1, 2014. BPJS of Health is a public legal entity that coordinates directly under the President and in 2019 all Indonesian people have to become JKN participants to make Universal Health Coverage (UHC). The purpose of this study was to study the JKN participant in 2019. This study used a descriptive type of research. The subject of this study is the all population of Indonesia. This study will discuss the number of JKN participants, types of JKN participation, rights and obligations, procedures for registration, cost, and how to use a National Health Insurance card. The results of this study show data from BPJS of Health on August 8, 2014 that National Health Insurance participants 126,487,166 people from total population 257,5 million. JKN participation continues to increase every year until 2019. Data from BPJS Health of JKN participants as of April 1, 2019 amounted to 219,669,453 people with a total PBI-APBN 96,517,386 people, PBI-APBD 35,925,726 people, PPU – PN 17,279,621 people, PPU-BU 33,187,465 people, PBPU 31,600,985 people, and Not Workers 5,158,270 people. In 2019 all Indonesia people became JKN participants. The conclusion that the number of JKN participants continued to increase, April 1, 2019 JKN participants 219.669.453 people from total population 257,5 million and in 2019 Indonesia be expected UHC. Suggestions this research, companies that have not yet register their employees in JKN and people have not yet become JKN participants are immediately register through the office / website BPJS of Health or care center 1500400, Mobile JKN, e-DABU.